Pengaruh Lingkungan Kerja, Parental Influence, dan Biaya Kuliah Terhadap Minat Mahasiswa Akuntansi di STIE Mahardika Surabaya pada Profesi Akuntan Publik - Saleh, Royyan; Harjanti, Wulandari; Rahardjo, Kusuma Adi (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
The objective of this study is to investigate how the work environment, parental guidance, and tuition costs impact the interest of accounting students. The research data source used was accounting students at STIE Mahardhika Surabaya, regular morning and regular evening A and evening B. The chosen method for data analysis was quantitative and descriptive. To gather 81 samples, a purposive sampling technique was employed. The findings of the study indicate that the environment at work (X1) and parental guidance (X2) positively and significantly impact the interest of accounting students at STIE Mahardhika Surabaya. However, tuition fees (X3) show a positive but insignificant effect on the students' interest. The determinant result (R2) of 0.566 suggests that the variables of work environment (X1), parental influence (X2), and tuition fees (X3) collectively influence the interest of accounting students at STIE Mahardhika Surabaya in the field of public accounting (Y) by 56.6%, leaving 43.4% to be explained by other factors.